Deeper competency-based learning: making equitable, student-centered, sustainable shifts - Hess, Karin J.; Colby, Rose; Joseph, Daniel A.; Corwin (Firm) (Thousand Oaks: Corwin, 2020)
"Competency-Based Education (CBE) can be loosely and simply defined as flexibility in awarding or earning credit. Fundamentally, CBE allows students to show progress as they demonstrate mastery of academic content regardless of time, place, or pace of learning. Competency-based strategies provide students with personalized learning opportunities, including online and blended learning, dual enrollment and early college high schools, project-based and community-based learning, and credit recovery. This type of education often leads to better student engagement because the content is relevant to each student and tailored to the student's unique needs. In addition, ESSA awards assessment grants to states who use CBE. It is also named in ESSA as an example of innovative assessment. All three authors have been at the forefront of implementing CBA across schools and districts, and in this book they share their best practices. They have seen schools struggling with how to get started and how to support and sustain the many shifts needed to move from more traditional curricula, instruction, assessment, and reporting to systems that require unique roles and new skill sets for school leaders, teachers, and students. The book will include a deep dive into the many facets that need to be considered for CBE to be successful, including the often neglected topics of communication with families, multi-year assessment plans, supporting PLCs, and student voice/choice"--
Introduction -- Chapter 1. The WHAT, the WHY, and the HOW of CBE -- Chapter 2. Making organizational shifts -- Chapter 3. Making shifts in teaching and learning structures -- Chapter 4. Making the shift to student-centered classrooms.
Includes appendices, glossary, bibliographical references and index.
Keywords: Competency-based education -- United States; Competency based education -- Curricula; Educational innovations -- United States; Educational change; Teachers -- In-service training; Teaching -- Methodology